2012
DOI: 10.1073/pnas.1207523109
|View full text |Cite
|
Sign up to set email alerts
|

Predicting errors from reconfiguration patterns in human brain networks

Abstract: Task preparation is a complex cognitive process that implements anticipatory adjustments to facilitate future task performance.Little is known about quantitative network parameters governing this process in humans. Using functional magnetic resonance imaging (fMRI) and functional connectivity measurements, we show that the large-scale topology of the brain network involved in task preparation shows a pattern of dynamic reconfigurations that guides optimal behavior. This network could be decomposed into two dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
144
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(153 citation statements)
references
References 48 publications
9
144
0
Order By: Relevance
“…These networks of regions with coherent activity during rest are consistent across subjects and closely resemble the brain's functional organization of evoked responses (Damoiseaux et al, 2006;Fox and Raichle, 2007;Laird et al, 2011;Smith et al, 2009). Coherent BOLD activity persists during sleep and in anesthetized monkeys, suggesting that it reflects a fundamental property of the brain's functional organization (Larson-Prior et al, 2009;Vincent et al, 2007).Coherent BOLD activity, known as "functional connectivity" (FC), is modulated by learning (Bassett et al, 2011), cognitive and affective states (Cribben et al, 2012;Ekman et al, 2012;Eryilmaz et al, 2011;Richiardi et al, 2011;Shirer et al, 2012) and also spontaneously Chang and Glover, 2010; Kitzbichler et al, 2009). Chang andGlover (2010) showed that FC between the posterior cingulate cortex, a key region of the default mode network, and various other brain regions was highly dynamic over time.…”
mentioning
confidence: 61%
See 3 more Smart Citations
“…These networks of regions with coherent activity during rest are consistent across subjects and closely resemble the brain's functional organization of evoked responses (Damoiseaux et al, 2006;Fox and Raichle, 2007;Laird et al, 2011;Smith et al, 2009). Coherent BOLD activity persists during sleep and in anesthetized monkeys, suggesting that it reflects a fundamental property of the brain's functional organization (Larson-Prior et al, 2009;Vincent et al, 2007).Coherent BOLD activity, known as "functional connectivity" (FC), is modulated by learning (Bassett et al, 2011), cognitive and affective states (Cribben et al, 2012;Ekman et al, 2012;Eryilmaz et al, 2011;Richiardi et al, 2011;Shirer et al, 2012) and also spontaneously Chang and Glover, 2010; Kitzbichler et al, 2009). Chang andGlover (2010) showed that FC between the posterior cingulate cortex, a key region of the default mode network, and various other brain regions was highly dynamic over time.…”
mentioning
confidence: 61%
“…Previous studies reported large-scale reorganizations of whole-brain functional brain networks during learning (Bassett et al, 2011), task preparation (Ekman et al, 2012), or rest (Allen et al, in press). Bassett et al (2011) studied dynamic community organization, Ekman et al (2012) predicted upcoming tasks and errors from network measures (e.g.…”
Section: Related Methodsological Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Functional connectivity (FC), which is estimated by correlation of BOLD activity, identifies coherent brain activity in distributed and reproducible networks. FC has revealed reorganization of brain networks during cognitive tasks (Ekman et al, 2012;Lewis et al, 2009;Richiardi et al, 2011Richiardi et al, , 2013Shirer et al, 2012), but also at rest (Allen et al, 2014;Chang and Glover, 2010;Hutchison et al, 2013b;Kang et al, 2011;Leonardi et al, 2013;Majeed et al, 2011;Smith et al, 2012). To study changes in FC over time sliding-window correlation analysis, where the correlation is estimated for brain activity during multiple, possibly overlapping temporal segments (typically 30-60 s), has been widely deployed (Allen et al, 2014;Chang and Glover, 2010;Hutchison et al, 2013a;Sakoglu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%